Assessment of treated wastewater irrigation using coconut fibre for spinach (Spinacia oleracea L.) vegetable plants - Ikenna, Odoemena Kenneth (2021)
This study focused on the assessment of urban wastewater for irrigation of vegetables after some degree of the quality enhancement of wastewater that is suitable for irrigation. The irrigation sector uses a vast amount of available freshwater resources. In urban areas, return flows from domestic uses can be reused for urban agriculture because of the availability of limited freshwater resources. Water and wastewater contain micro-nutrients such as oil, nitrogen and other harmful components. If the wastewater used for long-term in agricultural fields, it contributes to overloading of heavy metals nutrients and some pathogens from wastewater. Therefore, this study assesses the utilization of treated wastewater for irrigated Spinach vegetables. The source of wastewater used for this study from the catchment of Tasik Sri Serdang. The objectives of this study are; (i) to design and fabricate the coconut fiber filtration system for wastewater treatment in irrigation use, (ii) to characterize the suitability of irrigation use of wastewater and treated wastewater usingWQI, and (iii) to assess the utilization of treated wastewater irrigation for growing Spinach vegetables. In order to achieve the specific objectives of the study, a simple coconut-fiber based wastewater filtration system was used for wastewater quality enhancement. Then, wastewater collected from Tasik Sri Serdang was analyzed physiochemical properties of water quality parameters in the laboratory before applying irrigation for Spinach vegetables. Six physiochemical parameters of Water Quality Index (WQI) were determined which include Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Dissolved Oxygen (DO), Ammonia Nitrogen (AN), and pH. In addition, the heavy metals contents in the wastewater were analyzed involving three major elements; Copper (Cu), Nickel (Ni) and Zinc (Zn). Application of treated wastewater was applied to grow Spinach and assessed the effects of treated wastewater on growing Spinach vegetables. The concentrations of the six physiochemical parameters of treated wastewater of 35.67 mg/L BOD (Class V), 120.93 mg/L COD (Class V), 6.8 mg/L DO (Class II), 63.73 mg/L TSS (Class III), 16.57 mg/L AN (Class V) and pH 6.53 (Class II) were determined. While the heavy metals Cu, Ni and Zn were revealed to have concentrations of 3.01, 1.21, and 9.23 mg/L respectively. After determining physiochemical properties of wastewater, the concentrations of six WQI parameters were reduced by mixing water and enhanced the water quality to 8.6mg/L BOD (75.9%, Class IV), 38.2 mg/L COD (68.4%, Class III), 7.33 mg/L DO(7.8%, Class I), 31.37 mg/L TSS (50.8%, Class II), 1.14 mg/L AN (93.1%, Class IV) and pH 7.17 (9.7%, Class I). Enhanced overall WQI value achieved from 46.3 to 74.0 after treatment. All physiochemical parameters were obtained at least Class IV and better which is suitable and safe for irrigation. Heavy metals contents also reduced to 0.05, 0.02 and 4.93 mg/L for Cu, Ni and Zn, with a reduction of 98.4%, 98.1%, and 46.5%, respectively, while electrical conductivity(EC) of wastewater was reduced from the range of 5.9 - 6.6 dS/m to the range of 0.5 - 2.1 dS/m after treatment with coconut fiber filtration. Besides, the hydroponic method was applied to grow Spinach vegetables. The height of planted Spinach identified a maximum of 6.1 cm compared to only 5.3 cm for 21 days when planting Spinach under raw wastewater conditions. Treated wastewater hydroponic produced 6 to 7 plants leaves while raw wastewater hydroponic produced less number of leaves (4 to 6). Moreover, the overall weight of Spinach grown under treated wastewater at the end of growing stageswas measured to be 0.8 kg, much greater than only 0.5 kg of Spinach grown under raw wastewater. Spinach leaves were more vigorous and vibrant when applying treated wastewater for planting. However, a slight of inhibition of plant growth and less vibrant color of the leaves were observed when raw wastewaterwas used. This study recommends that treated wastewater using low-cost wastewater filtration system is feasible for urban vegetables irrigation.